Asymptotic Dichotomy in a Class of Third-Order Nonlinear Differential Equations with Impulses - Kun-Wen Wen; Gen-Qiang Wang; Sui Sun Cheng (Abstract and Applied Analysis)
Solutions of quite a few higher-order delay functional differential equations oscillate or converge to zero. In this paper, we obtain several such dichotomous criteria for a class of third-order nonlinear differential equation with impulses.